OPTIMALISASI SISTEM ANTRIAN PELANGGAN PADA PELAYANAN TELLER DI KANTOR POS (STUDI KASUS PADA KANTOR POS CABANG SUKOREJO KENDAL) - Diyan Mumpuni; Bambang Irawanto (MATEMATIKA FSM, UNDIP, 2014)
ABSTRAK. The problem occurs because there is a queue length of the queue at service facilities, or the presence of maids who are unemployed at the time of service due to vacancy queue. Services providers that can not be separated from the issue queue is the Post Office. queuing theory is used to determine the queuing model that can represent the state at the service counter, and to optimize the service time at the service counter. Queuing model of optimal service counter at the Post Office is model queue. The highest number of customer arrivals during the study time on each date that is 20, if model is applied on these days can lead to a buildup of the queue, so the queue model is used to optimally serve the customer every 20 is model queue.